Opioids and Their Receptors Present and Emerging Concepts in Opioid Drug Discovery II - Spetea, Mariana; van Rijn, Richard M. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Few neurotransmitter systems have fascinated as much as the opioid system (i.e., opioid ligands and their receptors). Over the years, scientific studies of the endogenous opioid system have uncovered a complex and subtle system that exhibits impressive diversity, based on its critical role in modulating a large number of sensory, motivational, emotional and cognitive functions. Additionally, its important therapeutic value for the treatment of many human disorders, including pain, affective and addictive disorders, and gastrointestinal motility disorders, has been of persistent interest. This book specifically covers a broad area of the opioid research, offering up-to-date and new perspectives about opioid drug discovery. The diversity among the discussed topics ranging from medicinal chemistry to opioid pharmacology, from basic science to translational research, is a testimony to the complexity of the opioid system that results from the expression, regulation and functional role of opioid ligands and their receptors. This book will serve as a useful reference to scientists while also stimulating continuous research in the chemistry and pharmacology of the opioid system, with the prospective for finding improved therapies of human diseases where the opioid system plays a central role.